How Beauty Determines Gaze! Facial Attractiveness and Gaze Duration in Images of Real World Scenes. (August 2016) - Leder, Helmut; Mitrovic, Aleksandra; Goller, Jürgen
We showed that the looking time spent on faces is a valid covariate of beauty by testing the relation between facial attractiveness and gaze behavior. We presented natural scenes which always pictured two people, encompassing a wide range of facial attractiveness. Employing measurements of eye movements in a free viewing paradigm, we found a linear relation between facial attractiveness and gaze behavior: The more attractive the face, the longer and the more often it was looked at. In line with evolutionary approaches, the positive relation was particularly pronounced when participants viewed other sex faces.